The Influence of Hedonic Motivation, Store Atmosphere and Positive Emotion on Consumer Impulse Buying - Hasanudin Alfahri; Endang Silaningsih; Yulianingsih (International Journal of Educational and Life Sciences, 2025)
This study aims to determine the effect of hedonic motivation, store atmosphere and positive emotion on consumer impulse buying. This study is a quantitative study with a survey method. The population in this study were consumers of the Nako Kuntum coffee cafe who had made at least one purchase. The results of this study indicate that: (1) Hedonic Motivation does not have a positive effect on impulse buying. (2) Store atmosphere does not have a positive effect on impulse buying. (3) Positive emotion has a positive effect on impulse buying.